2004
DOI: 10.1243/0954411042632117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foot sole hardness, thickness and footwear on foot pressure distribution parameters in diabetic neuropathy

Abstract: This paper presents details of the study undertaken to find the effects of foot sole hardness, thickness and footwear on walking-foot pressure distribution parameters (power ratio (PR)) in diabetic neuropathy. The foot sole hardness is characterized by Shore level. PR represents the ratio of high-frequency power to the total power in the power spectrum of the walking-foot pressure image distribution obtained from the optical pedobarograph. Spatial frequency distributions in the walking-foot pressure images wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 16 publications
1
45
2
Order By: Relevance
“…Their studies showed that all measured parameters had considerable influence on the development of plantar ulcers. The effects of foot sole hardness, thickness and footwear on walking-foot pressure distribution parameters (power ratio (PR)) in diabetic neuropathy were studied [14]. They showed that, providing microcellular rubber insole footwear based on optimum hardness and thickness was helpful in healing plantar ulcers in three to 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Their studies showed that all measured parameters had considerable influence on the development of plantar ulcers. The effects of foot sole hardness, thickness and footwear on walking-foot pressure distribution parameters (power ratio (PR)) in diabetic neuropathy were studied [14]. They showed that, providing microcellular rubber insole footwear based on optimum hardness and thickness was helpful in healing plantar ulcers in three to 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Prabhu et al [24] have analyzed the plantar pressure distribution in the diabetic neuropathy subjects in the frequency domain. Recently, Jacob et al [25] and Charanya et al [26] have evaluated different parameters like power ratio, foot sole hardness, foot sole soft thickness for diabetic neuropathic subjects. And they found that, the power ratio is more for the diabetic neuropathic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that increases in the order of 137-337% in A 1 and 88-131% in H 1 occur, corresponding to 66.7 and 200% increases in the Shore values, respectively, in foot sole areas 5 (first MTH) and 8 (big toe). This shows that, for area 8, compared with other m'eas, changes in Shore level are reflected as larger changes in the respective tissue texture and therefore a larger incidence of ulcers in this area, as shown by CHARANYA et al (2004b).…”
Section: Discussionmentioning
confidence: 76%